A Case-Control Study of the Factors Associated with Anemia in Chinese Children Aged 3–7 years Old. (20th March 2023) - Mou, Jinsong; Zhou, Haishan; Feng, Zhangui; Huang, Shiya; Wang, Zhaohui; Zhang, Chaoyu; Wang, Yudong
Abstract : Background . Anemia in children is still an important public problem in China and can have a profound impact on the physical and mental health of children. The purpose of this study was to explore the risk factors for anemia among Chinese children aged 3–7 years old and to provide some basis for the prevention and control of anemia. Methods . A matched case-control study was conducted and 1104 children (552 cases and 552 controls) were recruited in this study. Cases were children who were diagnosed with anemia by the doctor of physical examination and checked by one deputy chief physician of pediatrics, and controls were healthy children without anemia. Data were collected using a self-designed structured questionnaire. Univariable and multivariable analyses were used to identify independent determinants of anemia. P values less than 0.05 were used to declare statistical significance. Results . In the multivariable analyses, maternal anemia before or during pregnancy and lactation (OR = 2.14, 95% CI: 1.10∼4.15; OR = 2.86, 95% CI: 1.66∼4.94; OR = 2.51, 95% CI: 1.13∼5.60), gestational weeks (OR = 0.72, 95% CI: 0.53∼0.96), having G6PD deficiency or thalassemia (OR = 8.12, 95% CI: 2.00∼33.04; OR = 36.25, 95% CI: 10.40∼126.43), having cold and cough in previous two weeks (OR = 1.56, 95% CI: 1.04∼2.34), family income (OR = 0.80, 95% CI: 0.65∼0.97), and being a picky eater (OR = 1.80, 95% CI: 1.20∼2.71) were determinants of anemia in children aged 3–7 years old. Conclusions . Some of the identified factors are modifiable and could be targeted to reduce childhood anemia. More emphasis should be given by the concerned bodies to intervene in the anemia problem by improving the maternal health education, screening for disease-related anemia, requesting medical services in a timely manner, improving the economic status of households, promoting dietary habits, and improving sanitation and hygiene practices.